Proteomics-Based RT-qPCR and Functional Analysis of 18 Genes in Metronidazole Resistance of Bacteroides fragilis - Alshateri Bakhtiyar (ANTIBIOTICS, 2024)
Previously, we reported that metronidazole MICs are not dependent on the expression levels of nim genes in B. fragilis strains and we compared the proteomes of metronidazole-resistant laboratory B. fragilis strains to those of their susceptible parent strains. Here, we used RT-qPCR to correlate the expression levels of 18 candidate genes in a panel of selected, clinical nim gene-positive and -negative B. fragilis strains to their metronidazole MICs. Metronidazole MICs were correlated with the expression of certain tested genes. Specifically, lactate dehydrogenase expression correlated positively, whereas cytochrome fumarate reductase/succinate dehydrogenase, malate dehydrogenase, phosphoglycerate kinase redox and gat (GCN5-like acetyltransferase), and relA (stringent response) regulatory gene expressions correlated negatively with metronidazole MICs. This result provides evidence for the involvement of carbohydrate catabolic enzymes in metronidazole resistance in B. fragilis. This result was supported by direct substrate utilization tests. However, the exact roles of these genes/proteins should be determined in deletion–complementation tests. Moreover, the exact redox cofactor(s) participating in metronidazole activation need to be identified.